Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{\sqrt{ab}-1}{3}=\frac{\sqrt{bc}-3}{9}=\frac{\sqrt{ac}-5}{-6}=\frac{\sqrt{ab}+\sqrt{bc}+\sqrt{ac}-9}{6}=\frac{1}{3}\)
\(\Rightarrow\left\{{}\begin{matrix}\frac{\sqrt{ab}-1}{3}=\frac{1}{3}\\\frac{\sqrt{bc}-3}{9}=\frac{1}{3}\\\frac{\sqrt{ac}-5}{-6}=\frac{1}{3}\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}\sqrt{ab}=2\\\sqrt{bc}=6\\\sqrt{ac}=3\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}ab=4\\bc=36\\ac=9\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}c=9a\\ac=9\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}a=1\\b=4\\c=9\end{matrix}\right.\)
= \(\dfrac{\sqrt{xy}-1+\sqrt{yz}-3+\sqrt{zx}-5}{3+9+6}\) = \(\dfrac{11-\left(1+3+5\right)}{18}\)=\(\dfrac{1}{9}\)
Bài1:
Ta có:
a)\(\sqrt{\dfrac{3^2}{5^2}}=\sqrt{\dfrac{9}{25}}=\dfrac{3}{5}\)
b)\(\dfrac{\sqrt{3^2}+\sqrt{42^2}}{\sqrt{5^2}+\sqrt{70^2}}=\dfrac{\sqrt{9}+\sqrt{1764}}{\sqrt{25}+\sqrt{4900}}=\dfrac{3+42}{5+70}=\dfrac{45}{75}=\dfrac{3}{5}\)
c)\(\dfrac{\sqrt{3^2}-\sqrt{8^2}}{\sqrt{5^2}-\sqrt{8^2}}=\dfrac{\sqrt{9}-\sqrt{64}}{\sqrt{25}-\sqrt{64}}=\dfrac{3-8}{5-8}=\dfrac{-5}{-3}=\dfrac{5}{3}\)
Từ đó, suy ra: \(\dfrac{3}{5}=\sqrt{\dfrac{3^2}{5^2}}=\dfrac{\sqrt{3^2}+\sqrt{42^2}}{\sqrt{5^2}+\sqrt{70^2}}\)
Bài 2:
Không có đề bài à bạn?
Bài 3:
a)\(\sqrt{x}-1=4\)
\(\Rightarrow\sqrt{x}=5\)
\(\Rightarrow x=\sqrt{25}\)
\(\Rightarrow x=5\)
b)Vd:\(\sqrt{x^4}=\sqrt{x.x.x.x}=x^2\Rightarrow\sqrt{x^4}=x^2\)
Từ Vd suy ra:\(\sqrt{\left(x-1\right)^4}=16\)
\(\Rightarrow\left(x-1\right)^2=16\)
\(\Rightarrow\left(x-1\right)^2=4^2\)
\(\Rightarrow x-1=4\)
\(\Rightarrow x=5\)
a: \(=7\cdot\dfrac{6}{7}-5+\dfrac{3\sqrt{2}}{2}=1+\dfrac{3}{2}\sqrt{2}\)
b: \(=-\dfrac{8}{7}-\dfrac{3}{5}\cdot\dfrac{5}{8}+\dfrac{1}{2}=\dfrac{-16+7}{14}-\dfrac{3}{8}=\dfrac{-9}{14}-\dfrac{3}{8}\)
\(=\dfrac{-72-42}{112}=\dfrac{-114}{112}=-\dfrac{57}{56}\)
c: \(=20\sqrt{5}-\dfrac{1}{4}\cdot\dfrac{4}{3}+\dfrac{3}{2}=20\sqrt{5}+\dfrac{3}{2}-\dfrac{1}{3}=20\sqrt{5}+\dfrac{7}{6}\)
Lời giải:
Đặt \(\frac{\sqrt{ab}-1}{3}=\frac{\sqrt{bc}-3}{9}=\frac{\sqrt{ca}-5}{-6}=t\)
\(\Rightarrow \left\{\begin{matrix} \sqrt{ab}=3t+1\\ \sqrt{bc}=9t+3\\ \sqrt{ca}=5-6t\end{matrix}\right.\)
\(\Rightarrow \sqrt{ab}+\sqrt{bc}+\sqrt{ca}=6t+9\)
\(\Leftrightarrow 11=6t+9\Leftrightarrow t=\frac{1}{3}\)
Khi đó : \(\left\{\begin{matrix} \sqrt{ab}=2\\ \sqrt{bc}=6\\ \sqrt{ac}=3\end{matrix}\right.\) \(\Rightarrow \left\{\begin{matrix} ab=4\\ bc=36\\ ac=9\end{matrix}\right.\Rightarrow abc=\sqrt{4.36.9}=36\)
\(\Rightarrow \left\{\begin{matrix} c=\frac{abc}{ab}=9\\ a=\frac{abc}{bc}=1\\ b=\frac{abc}{ac}=4\end{matrix}\right.\)
Vậy....